Peran Dinas Perindustrian dan Perdagangan Kota Batam dalam Melakukan Pemberdayaan Masyarakat: Studi pada Kelompok Pengrajin Kain Tenun Pulau Ngenang Kota Batam - Fifit Hidayuwati; Fitri Kurnianingsih; Firman Firman (Jurnal Media Administrasi, 2024)
In the Riau Islands, especially on Ngenang Island, weaving activities have become part of the life of the Malay community. This initiative to develop and produce woven fabric aims to preserve culture as well as empower women and improve the local economy. This research aims to determine the role of the Batam City Department of Industry and Trade (Disperindag) in empowering the community through groups of woven cloth craftsmen on Ngenang Island. This research uses a qualitative descriptive research method. The data sources for this research come from primary and secondary data. Research results based on (1) support the development of small and medium industries (IKM), including the weaving industry. (2) empowerment efforts carried out through guidance and technical support, which helps in developing technical skills and innovation in woven motifs (3) the government responds quickly to the needs of craftsmen by providing funds, looms and raw materials, increasing production efficiency and quality of woven fabrics resulting from. In conclusion, the role of the government on Ngenang Island is not only as a regulator, but also as a dynamist and facilitator in strengthening the weaving industry as part of an inclusive and sustainable local economic development strategy.